Selenate and selenite affect photosynthetic pigments and ROS scavenging through distinct mechanisms in cowpea (Vigna unguiculata (L.) walp) plants - Silva, Vinicius Martins [UNESP] (2020)
Selenium (Se) is a beneficial element to higher plants. Application of Se at low concentrations enhances the antioxidant metabolism reducing the reactive oxygen species (ROS) generated by plant membrane cells. This study aimed to evaluate how the application of Se in the forms sodium selenate and sodium selenite regulates ROS scavenging in field-grown cowpea plants. Seven Se application rates (0; 2.5; 5; 10; 20; 40 and 60 g ha−1) of each of the two Se forms were applied to plants via the soil. Photosynthetic pigments concentration, gas exchange parameters, lipid peroxidation by malondialdehyde (MDA) concentration, hydrogen peroxide concentration, activity of catalase (CAT, EC:1.11.1.6), glutathione reductase (GR, EC:1.6.4.2), ascorbate peroxidase (APX, EC:1.11.1.11) and Se concentration in leaves and grains were evaluated. In general, Se application led to a decrease in chlorophyll a concentration whilst leading to an increase in chlorophyll b, indicating conservation of total chlorophyll concentration. Application of 2.5 g ha−1 of Se as selenate provided a notable increase in total chlorophyll and total carotenoids compared to the other application rates. Selenate and selenite application decreased lipid peroxidation. However, each Se source acted in a different pathway to combat ROS. While selenate showed more potential to increase activity of APX and GR, selenite showed a higher potential to increase CAT activity. The negative correlation between CAT and GR is indicative that both pathways might be activated under distinct circumstances. The more prominent activity of CAT under high rates of selenite resulted in a negative correlation of this enzyme with chlorophyll a and carotenoids. Both selenate and selenite application increased sucrose and total sugars concentration in leaves of cowpea plants. Overall, these results indicate that application of Se in cowpea under field conditions stimulates distinct pathways to scavenge ROS. This could prove beneficial to mitigate oxidative stress during plant development.